RANCANG BANGUN GAME EDUKASI PETUALANGAN SI BADOL - Ghazali, Zulfikar (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2014)
Education is a tool to guide someone into good person especially religious education. Islamic education in particular regarding the basic knowledge of Islam has been introduced when the students sit in Class I to Class VI of elementary school level. But in the era globalization, we still found the naughtiness of teenager or children who far from noble character such as disobedient to the parents and teachers, often fighting, stealing and etc. One of the factors that caused the children have bad personality is less embedded of religious soul on each person in society. Based on these problems were built an Islamic educational game that expected to contribute to society and children as an alternative media in delivering learning about the science of religion especially Islam religion, so that after playing this game the player can know and inflict the spirit to study Islam religion. In this educational game, there are elements learning by doing (learning while playing) which combines three learning methods, namely the demonstration method, story method, and play method. The results showed that the design and testing of educational adventure game "Si Badol" can be used and understood by the user.